PLANNING FOR TEACHING AND LEARNING: UNDERSTANDING AND WORKING WITH SYLLABI AND CONSTRUCTING EFFECTIVE LESSON PLANS IN SCHOOLS, LYCEUMS, AND COLLEGES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article discusses the significance of planning in teaching and learning, focusing on how educators work with syllabi in schools, lyceums, and colleges. It highlights the role of the syllabus in guiding instruction and outlines the key components of effective lesson planning. The article emphasizes alignment between curriculum goals and classroom activities to support student learning and teacher effectiveness.